Adaptive strategies for inland touristic destinations (Sil Canyon, Galicia, Nw Spain) - De Uña-Álvarez, Elena; Villarino-Pérez, Montserrat (Cuadernos de Turismo, 2017)
Tourism potential is greatly related to destinations’ reorganization and innovation abilities. Throughout the last fifteen years, tourism evolution at the western section of the Sil Canyon (NW Spain) has reflected the transformations facing times of crisis. By assuming tourism as a complex adaptive system, the aims of this research about an inland destination were focused on the touristic strategies interpretation. The destination evolution is carried out, including the narratives by key actors. The rural tourism strategies change by integrating nature-based and cultural tourism strategies.